KEARIFAN LOKAL BUDAYA JAWA DALAM PERSPEKTIF PANCASILA - Franciscus Xaverius Wartoyo (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Pancasila as one of the pillars of support in the life of the nation and state has concepts, principles and values which are the crystallization of the system of various local regions of the Indonesian nation, giving color to each regional system that is manifested nationally and makes it Unity in Diversity. This article examines local wisdom in particular, Java towards the values of Pancasila as a unifying nation. Research approach with library studies and historical analysis. The five precepts in Pancasila show fundamental ideas about humans and their entire reality in life along with differences in ethnicity, race, religion, culture and unity complementing one another wrapped in a framework of diversity in mutual cooperation in accordance with Javanese cultural concepts, which are believed to be true by the Indonesian people and sourced from the character, Indonesian culture and underlying the establishment of the State of Indonesia. In short, the formulation of the Pancasila is a formula obtained from the